Mentoring strategies to support diversity in research-focused junior faculty: A scoping review - Joni S. Williams; Rebekah J. Walker; Kaylin M. Burgess; L. Aubree Shay; Susanne Schmidt; Joel Tsevat; Jennifer A. Campbell; Aprill Z. Dawson; Mukoso N. Ozieh; Shane A. Phillips; Leonard E. Egede (Journal of Clinical and Translational Science, 2023)
Abstract